(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
The purpose of this research is to determine the relationship between perceptions about covid-19 and compliance with the application of new habits to prevent the corona virus in sungaisibam village, pekanbaru city. This research used descriptive correlation design with cross sectional approach. The Study was conducted in sungaisibam village, Pekanbaru city on 139 people who applied the adaptation of new habits and were taken through purposive sampling by taking into account the inclusion criteria. The measuring instrument was questionnaire that had been tested for validity and reliability. The analysis used are univariate and bivariate used alternative Chi Square Test. The Result of the study show that there is a significant relationship between perception and compliance with application of new habit adaptations to prevent transmission of the corona virus (p value 0,029). The result of this study recommend to the community in the sibam river to increase compliance with the adaptation of new habits, in the form of applying The 5M (Washing hands, using mask, avoiding crowds, keeping distance and reducing mobility)